Emergency consultations in obstetrics: identification of decisive, contributing and associated factors - Mair, Katharina; Nees, Juliane; Hoffmann, Janine; Bruckner, Thomas; Haun, Markus W.; Maatouk, Imad; Stepan, Holger; Schott, Sarah (Archives of gynecology and obstetrics, 2020)
Psychosocial and biological factors influence the perception of physical changes during pregnancy. Some pregnant women present to the obstetric emergency department (ED) with diverse symptoms not requiring urgent medical action. These visits result in over-consultation, tying up resources and inflating health care expenses. This study outlines factors associated with multiple ED visits during pregnancy, measures the prevalence of anxiety and depression, and explores the choice of maternity clinic for delivery aiming to elucidate options for care strategies.
Gesehen am 13.09.2021